Desain LKS Berbasis Virtual Laboratory Melalui ICT pada Materi Keseimbangan Benda Tegar, Elastisitas, dan Fluida Statis di Kelas XI - Hazrati Ashel; Hidayati Hidayati; Masril Masril; Yenni Darvina (PILLAR OF PHYSICS EDUCATION, 2018)
Physics learning in Curriculum 2013 requires teachers to implement all competencies. Attitude competence attaches to the knowledge competence and skill competence. Knowledge competence is obtained through the process of learning in the classroom, while the skill competence is obtained through practicum activities. The reality in school shows that not all teachers do skill competence such as practicum implementation. This is due to the lack of tools and materials and the unavailability of worksheet that has a scientific approach that can be used as orientation for practicum implementation. One solution that can be done is to develop worksheet based on virtual laboratory through ICT. The purpose of this research is to determine the validity and practicality of worksheet based on the virtual laboratory through ICT on the material balance of rigid body, elasticity, and static fluid in class XI SMAN 1 Padang. The type of this research  is Research and Development (R&D). The object of this research is worksheet based on virtual laboratory through ICT on the balance material of rigid body, elasticity, and static fluid. The instrument of data collector used is validation test and practicality test sheet. Data analysis technique used is validity test analysis and  practicality test analysis. Based on the data analysis that has been done, obtained the value of validity and  practicality of product that have been developed. This product has a validity value of 90.44. The value of product practicality according to the teacher is 88.46 whereas according to the student is 87.14. This value indicates that worksheet based on virtual laboratory through ICT is valid and practical use in learning.